EyeOnTree: sistema IoT de monitoramento de florestas de celulose utilizando ESP32-CAM e Telegram - OLIVEIRA, Jorge Lucas de; MENEZES, Kauê Balbino de; SOUZA, Nicolas Henrique Izaias de; GOMES, Rafael Cecílio (098, 2025)
O projeto em questão consiste em um sistema de monitoramento de florestas de celulose/silvicultura contra incêndios. Este sistema opera por meio do módulo câmera ESP32-CAM com inteligência artificial integrada, em conjunto com uma plataforma de prototipagem baseada em ESP32. A transmissão e recebimento de dados são realizados via conexão Wi-Fi entre os módulos ESP32-CAM, ESP32 e o aplicativo de mensagens Telegram.

The project in question consists of a monitoring system for pulpwood forests/forestry against fires. This system operates through the ESP32-CAM camera module with integrated artificial intelligence, together with a prototyping platform based on ESP32. This system operates through the ESP32-CAM camera module with integrated artificial intelligence, in conjunction with a prototyping platform based on ESP32. Data transmission and reception are carried out via a Wi-Fi connection between the ESP32-CAM and ESP32 modules and the Telegram messaging application.
EyeOnTree: IoT system for monitoring pulp and paper forests using ESP32-CAM and Telegram
Keywords: Inteligência artificial; Internet das coisas; Microcontrolador; Controle e Processos Industriais